2017
DOI: 10.1038/ncomms14443
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive translational regulation of the cell signalling circuitry underlies mammalian development

Abstract: The degree and dynamics of translational control during mammalian development remain poorly understood. Here we monitored translation of the mammalian genome as cells become specified and organize into tissues in vivo. This identified unexpected and pervasive translational regulation of most of the core signalling circuitry including Shh, Wnt, Hippo, PI3K and MAPK pathways. We further identify and functionally characterize a complex landscape of upstream open reading frames (uORFs) across 5′-untranslated regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 35 publications
(48 reference statements)
4
51
0
Order By: Relevance
“…Our study of ribosome heterogeneity within mESCs therefore serves as a foundation to future research. For example, a recent study has revealed tissue-specific programs of translational control during mammalian embryonic development (Fujii et al, 2017). An important immediate question is to determine whether a selective translational landscape of specific types of ribosomes bearing or missing certain RPs exists during the course of cellular differentiation and between different cell and tissue types where the degree of ribosome heterogeneity could be even more extensive.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of ribosome heterogeneity within mESCs therefore serves as a foundation to future research. For example, a recent study has revealed tissue-specific programs of translational control during mammalian embryonic development (Fujii et al, 2017). An important immediate question is to determine whether a selective translational landscape of specific types of ribosomes bearing or missing certain RPs exists during the course of cellular differentiation and between different cell and tissue types where the degree of ribosome heterogeneity could be even more extensive.…”
Section: Discussionmentioning
confidence: 99%
“…While identity of those mRNAs has to be determined by future experiments, one should mention that many key components of the PI3K/MTOR signaling pathway appear to have highly inefficient translation initiation, at least, in mouse embryonic stem cells (Fujii et al . ). Interestingly, reduced activity of the PI3K/MTOR pathway was observed after inhibition of neuronal ribosome synthesis (Slomnicki et al .…”
Section: Consequences Of Dysregulated Ribosomal Biogenesis In the Devmentioning
confidence: 97%
“…Finally, establishing antibodies that can recognize site-specific PTMs will help to understand the distribution of these RP PTMs within different tissues, during different physiological states, or during the course of embryonic development. It has been recently shown that translation of the mammalian genome is intricately controlled in space and time [87]. The approaches outlined here to identify RP PTMs and to characterize their functional consequences are likely to reveal the potential dynamics of how ribosome modifications may directly influence protein expression within cells and developing organisms.…”
Section: Ubiquitin Comes In Various Sizes and Shapes At The Ribosomementioning
confidence: 99%